Characterization of bilayer AZO film grown by low-damage sputtering for Cu(In, Ga)Se2 solar cell with a CBD-ZnS buffer layer. (July 2018) - Lee, Woo-Jung; Cho, Dae-Hyung; Wi, Jae-Hyung; Han, Won Seok; Kim, Boo-Kyoung; Choi, Sang Dae; Baek, Ju-Yeoul; Chung, Yong-Duck
Abstract: Chemical bath deposition (CBD)-ZnS is used as a buffer layer for Cu(In, Ga)Se2 (CIGS) solar cell and then, plasma damage originated from the negative oxygen ions or neutral particles with high energy is regarded as an important issue during subsequent deposition of window layer by sputtering process. To avoid negative plasma effects, we newly designed sputtering system with dual deposition mode of low damage sputtering (LDS) process and direct sputtering (DS) process, adjusting plasma direction by dual cylindrical targets. It allows to grow bilayer AZO film by sequentially depositing thin LDS AZO film as a protect layer and thick AZO film as a transparent conducting layer to collect electrons. The physical and electrical characteristics of bilayer AZO film were investigated to verify the positive effect against plasma damage. In plasma damage test using GaAs wafer, we observed that increase of sputtering power leads to a falling-off in electrical qualities by plasma damage. For practical solar cell application, we fabricated three types of CIGS/CBD-ZnS solar cells with LDS AZO film grown at 2 kW and 5 kW (by 1500 mm cylindrical targets) and Conventional-AZO film (by 4-in. circular targets), and demonstrated that the performance of CIGS solar cell with LDS AZO is superior to that with Conventional-AZO film due to the effective protection layer to relieve plasma damage.